Meeting report: an exploration into the scientific and regulatory aspects of pharmaceutical drug quality in the United States. Issue 2 (1st February 2022) - Flavin, Bridget M.; Happe, Laura E.; Hatton, Randy C.
ABSTRACT: Introduction: The University of Florida College of Pharmacy, Department of Pharmaceutical Outcomes and Policy hosted a seminar 6–7 March 2021, on the quality of pharmaceutical products in the United States. This meeting report summarizes the topics presented at the seminar and highlights the expert opinions offered by the presenters. Areas Covered: The seminar, held virtually due to the COVID-19 pandemic, included slide presentations and faculty-moderated panel discussions from experts in the field. These experts from regulatory, academic, and private sectors discussed bioequivalence standards, existing and emerging efforts to promote quality in brand and generic manufacturing, as well as market-based solutions throughout the drug supply chain. Expert Opinion: The time spent understanding bioequivalence standards during the seminar felt especially important and relevant in our current pandemic environment, given the present need to have confidence in the science of drug development and to advocate for the safety of pharmaceuticals. Also an important point to emphasize from the seminar, was that every stakeholder along the drug supply chain has a responsibility to do their part to maintain its quality. And those in attendance, many of whom were students of healthcare sciences, were encouraged to be leaders in their fields and develop strategies to advance innovative improvements.